Indicative value and training set of freshwater organic-walled algal palynomorphs (non-pollen palynomorphs). (15th April 2022) - Stivrins, Normunds; Trasune, Liva; Jasiunas, Nauris; Kalnina, Laimdota; Briede, Agrita; Maksims, Alekss; Steinberga, Dace; Jeskins, Jurijs; Rendenieks, Zigmars; Bikse, Janis; Kalvans, Andis; Lanka, Anna; et al.
Abstract: Only a few studies have related modern non-pollen palynomorphs to environmental variables, limiting the development of non-pollen palynomorphs training sets. Here, we perform substantial groundwork by developing a training set for freshwater organic-walled algal palynomorphs. We sampled surface sediments from 78 waterbodies across Latvia in north-eastern Europe with the aim of gaining information on the distribution and diversity of algal palynomorphs. We analysed the preferred living conditions (water and sediment properties) of algal palynomorphs in conjunction with climate and catchment characteristics (Quaternary sediment type, landscape usage, and composition). In total, 94 species/taxa belonging to four phyla (Cyanobacteria, Chlorophyta, Charophyta, and Ochrophyta) were identified. By applying statistical and descriptive analyses, we showed the indicative value of algal palynomorphs along various gradients. Using the established training set, we for the first constructed organic-walled algal palynomorphs-based pH and electric conductivity reconstructions for two lakes where natural and anthropogenic variability was recognised. Freshwater algal palynomorphs assemblages constrained by environmental and climatic variables open new horizons for further non-pollen palynomorphs qualitative and quantitative research. Highlights: First freshwater algal palynomorphs (non-pollen palynomorphs) based reconstructions have been made. Modern living conditions were studied and interpreted from the natural and anthropogenic waterbodies in Northeastern Europe. Quaternary sediment is important for abundance of certain algal palynomorphs. Human induced environmental changes override climatic parameters.